Size Fractionation of Metal Nanoparticles by Membrane Filtration - Akthakul, A.; Hochbaum, A. I.; Stellacci, F.; Mayes, A. M. (Advanced materials (Weinheim), 2005)
A novel thin film composite nanofiltration (NF) membrane is fabricated by coating a conventional ultrafiltration membrane with a self‐assembling amphiphilic graft copolymer. The NF membranes are used in the fractionation of gold nanoparticles to achieve a well‐defined particle cutoff diameter and reduced size dispersity (see Figure).